The concepts of a deportee and deportation in Lithuanian during the period of Soviet occupation: legal, ideological, administrative and social aspects - Kareniauskaitė, Monika (Genocidas ir rezistencija, 2018)
The subject of the article is the phenomenon of population transfer organized by the Soviets – deportations. The aim is to analyse and deconstruct the concepts of a deportee, deportation and exile using insights and methods of different scientific disciplines (sociology, history, law). The phenomenon of Soviet deportations is viewed from the perspective of a variety of sources and through examination of different source groups: Soviet sources of criminal law, administrative documents of the Lithuanian Communist Party, criminal court files and files of deportees, diaries and memoirs of the deportees themselves. The main question raised by the article is whether the legal status and actual situation of a deportee differed from that of a political prisoner. Could there a strict distinction be drawn between these two groups of repressed people in the Soviet system? In what circumstances the legal and factual situation of a “deportee” and “political offender” was similar?